Feeding Strategies During Natural Calamities - Bakshi, M.P.S.; Wadhwa, M.; Makkar, H.P.S. (Indian Journal of Animal Nutrition, 2018)
India is one of worst disaster prone countries of the world. Out of 36 states and union territories in the country, 25 of them are disaster prone. Disasters continue to occur without warning and are on an increase in their magnitude, complexity, frequency and economic impact. The natural calamities in the form of floods, tsunamis, famines, cyclones, earthquakes and avalanches are considered mainly due to global warming. The major effects are acute shortages of food, feed and fodder and drinking water which adversely affect human and livestock health and nutrition. Severe malnutrition due to natural calamities may depress growth, productive and reproductive performance. Therefore, while developing the feeding strategies during natural calamities, the first priority should be to save the animals from starvation, diverting feedstuffs from lactating animals and then to sustain productivity of the animals that survived to the extent possible. The water requirement of lactating cattle is in the range of 2.5-4.5 L/kg DM intake. During water scarcity, the watering frequencies in large ruminants should be decreased to once in 2-3 days which increase the retention time and in turn digestibility of nutrients. All affected animals should be shifted to restricted feeding which will reduce the volume and metabolic activity of the viscera and other tissues and in turn basal metabolism. Feed restriction increases the extent of negative energy balance and causes transient increases in concentrations of non-esterified fatty acids, acetate and ÃŸ-hydroxybutyrate in plasma due to the mobilization of nutrients from body reserves. The restricted feeding may cause loss in body weight and milk yield in lactating animals but ensures animals survivability.The strategies such as 1) restricted feeding; 2) conserved fodders in transportable silage bags; 3) fodder produced in low-cost hydroponic systems; 4) unconventional feed resources including propagation of thornless cactus; 5) urea molasses multinutrient blocks; 6) hay bales, 7) densified complete feed blocks or pellets containing untreated or urea-treated straws/stovers, tree leaves and grasses, mushroom harvested spent straw with and without feed additives could help prevent livestock mortality and morbidity in emergency situations. Once the availability of quality feed and fodder improves, the animals should be given compensatory feeding. The animals will recoup the loss in body weight completely and partly the production performance suffered during natural calamities.